162 Whole-body cryotherapy treatment modulates the innate immune response in non-professional football players. (8th December 2021) - Selleri, Valentina; De Gaetano, Anna; Zanini, Giada; Malerba, Mara; Pinti, Marcello; Tripi, Ferdinando; Mattioli, Anna Vittoria; Savino, Gustavo; Nasi, Milena
Abstract: Aims: Whole-body cryotherapy (WBC) is a recently widely strategy used for muscle recovery after injury that can to activate inflammatory response. WBC consists of short exposure, of about 2-3 minutes, to dry air at cryogenic temperatures up to -190 °C. The aim of our study is to analyze WBC effects on metabolic, hormonal, and immunological responses of non-professional football players (NPFPs). Methods and results: Nine male NPFPs (age: 20 ± 2 years) on the same team are recruited and, in particular, they played and trained each day before, during, and after WBC treatment. We collected NPFPs blood samples immediately before WBC and after 5 once-day sessions, then we evaluated a set consisting of 50 analytes, including hormones profile, haematologic parameters, and serum chemistry. We proceeded with monocytes (Mo) phenotyping and then we investigated the concentration of some plasmatic markers with anti-inflammatory effects (IL2RA, IL1RN) or typically increased during inflammation [CCL2, IL-18, free mitochondrial DNA (mtDNA)]. WBC treatment (WBC-t) lead to a decrease not only in mean platelet volume, mean corpuscular haemoglobin, and ferritin levels, but also in testosterone and estradiol levels, even if they remain within the normal ranges. This treatment is also responsible for total Mo increased and, in particular, a reduction of classical Mo has been demonstrated in parallel with an increase of non-classical ones. Moreover, each Mo subset shows lower expression of CXCR4. Considering pro-inflammatory molecules, IL1RA showed a tendency to decrease, while IL1RN and IL18 decreased in plasma after WBC-t. Conversely, circulating mtDNA levels appeared unaltered by treatment. Conclusions: The differences detected in monocyte subset after WBC-t suggest that, in this condition, Mo could be redistributed into the surrounding tissue. In addition, CXCR4 reduction in Mo subsets could be due to their differentiation process. Hence, WBC could promote Mo differentiation through a mechanism that is still unknown. Since WBC seems to regulate the innate immune system in the enrolled NPFPs, it could have a role in tissue repair beyond a beneficial anti-inflammatory effect.